1988
DOI: 10.1007/bf01541743
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of experimenter effects on responses to a sex questionnaire

Abstract: To test whether responses to sex questionnaires vary as a function of the milieu in which the questionnaires are administered, university and college students were presented with an explicit sex questionnaire by a psychologist or by a member of the clergy. In the first study conducted at a nondenominational university, students generally responded similarly when tested by a psychologist, a rabbi, or a priest. There was some evidence suggesting that a greater number of students tested by members of the clergy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, the reliability and validity of the data collected by means of questionnaires are jeopardized by intentional non-reporting or overreporting, incomplete recall, misunderstanding of survey questions, and selective participation [25]. When socially sensitive information regarding sexual behavior is sought, the manner in which the data are collected could seriously distort research findings.Yet, under testing situations common to a number of studies, responses to sex questionnaires seem relatively unaffected by experimenter effects [28]. It has been reported that patients tend to give a more complete sexual history in a face-to-face interview with someone they come to know over time [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reliability and validity of the data collected by means of questionnaires are jeopardized by intentional non-reporting or overreporting, incomplete recall, misunderstanding of survey questions, and selective participation [25]. When socially sensitive information regarding sexual behavior is sought, the manner in which the data are collected could seriously distort research findings.Yet, under testing situations common to a number of studies, responses to sex questionnaires seem relatively unaffected by experimenter effects [28]. It has been reported that patients tend to give a more complete sexual history in a face-to-face interview with someone they come to know over time [7].…”
Section: Discussionmentioning
confidence: 99%
“…One contextual variable that has not generally been thought to be of great concern is the sex of the person administering the questionnaire in an anonymous, self-report survey (Johnson & Moore, 1993;Tourangeau & Smith, 1996). Indeed, Winer, Makowski, Alpert, and Collins (1988) have demonstrated that college student responses on an anonymous sex survey were generally not affected by the nature of the researcher even if the questionnaire had been administered by a religious leader. Therefore, sex researchers have not been particularly concerned with the sex of the questionnaire administrator, although Ehrhardt (1997) indicated that, with respect to face to face interviews, researchers are reaching a consensus that female interviewers are able to elicit more responses from participants than male interviewers and therefore "may be preferred to men" (p. 361).…”
Section: Sex Of Experimentermentioning
confidence: 95%